Study of Drugs for Gunma Rogam Used by Siddha Physicians in Jaffna District - Thayalini, T.; Sivagnanamany, P. (Bandaranaike Memorial Ayurvedic Research Institute Navinna, Maharagama, 2015)
Gunma rogam or its closed modern counterpart disease, peptic ulcer is one of the common diseases that affect people worldwide. The patient with Gunma rogam suffers from indigestion, pain, burning sensation in the stomach after intake of food and vomiting. It affects the physical and mental health simultaneously. Most of the people are affected mentally and socioeconomically due to many factors prevailing in the Jaffna District. This leads to a high incidences of Gunma rogam. Hence a study was conducted to identify the common drugs used by the physicians to treat gunma rogam. A cross sectional study was conducted in 40 Sidda physicians in 4 MOH divisions in the Jaffna district. The physicians used 58 drugs in different forms to treat Gunma rogam. Of the 58 drugs, 21(36%) are chooranam, 9(16%) are lehiyams, 5(9%) are decoctions, 4(7%) Melugu, 4 (7%) Chendoorams, 4(7%) Marthirai, 4(7%) Paspams, 3 Asavams, 2 Sharams, one Thiravakam and one Syrup. These drugs are used in combinations. Seven are identified as common drugs; Baskara lavana chooranam, Sangu paspam, Piththasamana laheyam, Adda chooranam, Hinguastaka chooranum, Vellai vengay kuligai and Malli chooranum. Most of these drugs contain salts (Uppukal) as a one of the ingredients. These salts help to neutralize the acidity. Most of the herbal ingredients possess Theepana, pasana and carminative action and help in digestion. The finding of the study helps in recognition of effective drugs used by the physicians
Keywords: Common drugs; Gunma rogam; Peptic ulcer; Siddha physicians